Assessing the benefits of green super rice in sub-Saharan Africa: Evidence from Mozambique - Kodama, Wataru; Pede, Valerien O.; Mishra, Ashok K.; Cuevas, Rosa Paula O.; Ndayiragije, Alexis; Cabrera, Ellanie R.; Langa, Marcos; Ali, Jauhar (Oxford University Press, 2022)
In Mozambique, smallholder farmers commonly grow rice under rainfed systems with limited fertilizer application; thus, productivity remains very low. Moreover, the adoption rate of improved rice varieties is as low as 3 per cent, partly because these varieties usually require an irrigated environment with the use of fertilizer. Green super rice (GSR) varieties are expected to sustain high yield potential under severe stress conditions. This article used farm-level survey data collected in Mozambique to assess the benefits of the adoption of a GSR variety (Simão) on the yield and cost efficiency of smallholder rice producers. The econometric approach involves propensity score matching and a simultaneous equation model with endogenous switching regression to account for observable and unobservable factors that affect adoption and outcome variables. The results indicate positive and significant benefits from adopting GSR on rice yield and cost efficiency for adopters. These benefits are observed not only in irrigated environments where fertilizer is applied together with some more advanced farming practices (i.e. Gaza province), but also in Nampula and Sofala provinces where farmers grow rice under rainfed conditions with no fertilizer application. Our findings suggest that GSR varieties have the potential to bring some positive changes in the development of rice production in Mozambique.